Developmental dyslexia: dysfunction of a left hemisphere reading network - Richlan, Fabio (Frontiers in Human Neuroscience, 2012)
This mini-review summarizes and integrates findings from recent meta-analyses and original neuroimaging studies on functional brain abnormalities in dyslexic readers. Surprisingly, there is little empirical support for the standard neuroanatomical model of developmental dyslexia, which localizes the primary phonological decoding deficit in left temporo-parietal regions. Rather, recent evidence points to a dysfunction of a left hemisphere reading network, which includes occipito-temporal, inferior frontal, and inferior parietal regions.